Bulked Segregant RNA-Seq Reveals Distinct Expression Profiling in Chinese Wheat Cultivar Jimai 23 Responding to Powdery Mildew - Zhu, Tong; Wu, Liru; He, Huagang; Song, Jiancheng; Jia, Mengshu; Liu, Liancheng; Wang, Xiaolu; Han, Ran; Niu, Liping; Du, Wenxiao; Zhang, Xu; Wang, Wenrui; et al. (Frontiers in Genetics, 2020)
Wheat powdery mildew, caused by Blumeria graminis f. sp. tritici (Bgt), is one of the most destructive fungal diseases threatening global wheat production. Host resistance is well known the most efficient method to control this disease. However, the molecular mechanism of wheat powdery mildew resistance (Pm) is still unclear. To preliminary analyze the molecular mechanism of Pm, the resistant wheat cultivar Jimai 23 was used to investigate its potential component and expression profiling responding to powdery mildew using bulked segregant RNA-Seq (BSR-Seq). The results showed that the Pm of Jimai23 was provided by a single dominant gene, tentatively designated PmJM23, and assigned to the documented Pm2 region of chromosome 5DS. A total of 3,816 consistently differential SNPs were called between resistant and susceptible parents and bulked pools derived from the combinations between the resistant parent Jimai23 and the susceptible parent Tainong18, of which 58 SNPs was assigned to the candidate region of PmJM23. Subsequently, 3,803 differentially expressed genes (DEGs) between parents and bulks were analyzed by GO, COG and KEGG pathway enrichment. The expression patterns of associated genes after Bgt infection were further determined by a time-scale qRT-PCR, and six disease-related genes were investigated their expression profiling during Bgt infection and might serve as valuable genetic resources for the improvement of durable resistance to Bgt.